The use of mobile-assisted virtual reality in fear of darkness therapy - Erick Paulus; Mira Suryani; Puspita Adhi Kusuma Wijayanti; Firdaus Perdana Yusuf; Aulia Iskandarsyah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Fear of darkness is a common psychological problem that may extent to a specific phobia if it is not treated well. Several intervention techniques related to fear and phobia using actual exposure therapy have been studied for decades, however, there were some constraints emerged when the therapist provides a real environment to overcome the patient's reaction to his/her specific fear. Virtual reality (VR) technology is an innovative tool providing a more immersive, secure, personal, and controlled virtual environment. Therefore, we developed a novel framework for treating the fear of darkness named Mobile-assisted Virtual Reality (MAVR). The purpose of this study was to evaluate the use of MAVR to treat fear of darkness based on usability, time consumption and its ability to decrease fear. We used the GOMS model as an interaction guidance between human and computer which aimed to facilitate the process of re-learning in mindset change and individual’s behavioral toward situation of darkness and night. Therefore, a comprehensive evaluation was conducted to measure the efficacy of the MAVR. We developed the usability assessment checklist to assess the feasibility and acceptability of the MAVR, and fear of darkness thermometer to measure the degree of fear. The Wilcoxon Signed Rank Test showed that the fear of darkness was significantly decreased after participants received the MAVR therapy (z=-3.550, p-value<0.001). We found that the MAVR was very useful, easy to be used and acceptable for participants. In conclusion, this study highlights the efficacy of Mobile-assisted Virtual Reality in treating specific fear, and it seems that Virtual Reality technology has a promising benefit to be implemented for other fear or specific phobia and also used in other psychological treatment.